The antibiotic procurement saga: a long-neglected stewardship target to combat antimicrobial resistance in Pakistan - Shairyar Afzal; Mishal Bajwa; Nabeel Ahmed; Jawaria Jabeen; Mian Shahzeb Haroon; Rana Muhammad Zahid Mushtaq; Zikria Saleem (Antimicrobial Resistance and Infection Control)
Abstract Background Consistent and timely access to antibiotics is a hallmark of an antimicrobial stewardship program (ASP) and can be achieved through good procurement practices. However, flawed procurement modules result in poor antibiotic supply management within health facilities of low- and middle-income countries (LMICs), including Pakistan, exacerbating antimicrobial resistance (AMR). This study seeks to understand hospital pharmacists’ perspectives on the antibiotic procurement process, its efficiency in ensuring consistent access to antibiotics, and the role of clinical pharmacists in rational procurement. Methods Semi-structured interviews with 24 purposively selected hospital pharmacists from secondary healthcare facilities in Punjab, Pakistan, were conducted utilizing a qualitative case study methodology. Data analysis was conducted using MAXQDA 2024 software, following a thematic analysis technique using a codebook approach to thematic analysis. Results The study identified five central themes: (1) The state of antibiotic use in hospitals is characterized by a lack of antibiotic use policy, resulting in mostly empirical and irrational prescribing practices. (2) Medicine availability significantly influences prescribing decisions, often taking precedence over clinical needs. (3) The procurement process, although structured, is flawed owing to rigid adherence to the Standard Medicine List (SML). (4) Rationality in procurement is compromised by disregard for AMR, with decisions driven more by cost and demand than clinical evidence. (5) The clinical acumen of pharmacists is underutilized in procurement due to multifarious barriers. Conclusion Antibiotic procurement is the mainstay of implementing an ASP in hospitals. This study elucidates significant policy, practice, and education gaps regarding antibiotic use and procurement in Pakistan. There is a critical need for comprehensive antibiotic policies, including a revision in SML, enhancing pharmacist authority in procurement decisions, more rational prescribing, and ensuring access to antibiotics through more informed and data-driven processes to combat AMR effectively.